New Mode of On- Line Automation: Chemilumino-Fluoro Metric Method for the Determination of Hydrogen Peroxide by Fluorescence Energy Transfer Using Ploy Acrylic Acid Gel Beads - M.A.Shakir, Issam (Iraqi Journal of Science, 2023)
Hydrogen peroxide was determined by a new , accurate , sensitive and rapid method via continuous mode of FIA coupled with total luminescence measurement which include the chemiluminescence generated ,based on the oxidation of Luminol which is loaded on poly acrylic acid gel beads by hydrogen peroxide in presence of Cobalt (II) ion as a chemiluminescence catalyst and the fluorescence that was created by the insitu radiation of the released chemiluminescence light. Fluorescien molecule was used as an accepter fluorophore where it is irradiated internally and instantly by the generation of luminol chemiluminescence light as internal source for irradiation of fluorescien molecule (Fluorescence Energy Transfer (FRET) ) . It can easily give fluorescence light (i.e , no external source for irradiation is used ) at λmax =530 nm. The method is based on the absorbance of the donor molecule (Luminol) by fourteen poly acrylic acid gel beads located in specially designed cell, this cell will measure instantly the emitted light (FRET) . A sample volume of 80 μL was used throughout the whole work. Linear calibration curve extend from 0.1 - 100 μMol .L-1 , with correlation coefficient of 0.9985 and limit of detection L.O.D (S/N =3) 217.60 pg/sample using step wise dilution of the minimum concentration that was achieved by the calibration graph. Repeatability (RSD%) of less than 0.5% for six successive measurement of 50 μMol .L-1 of hydrogen peroxide. The method was applied successively in determination of hydrogen peroxide in some pharmaceutical disinfectants